Badania satysfakcji użytkowników Biblioteki Uniwersytetu Zielonogórskiego składnikiem kultury oceny w nowoczesnej bibliotece akademickiej = User satisfaction surveys at the Zielona Góra University Library, as a component of a modern academic library evaluation culture - Banaszewski, Kamil; Bartosiak, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The multiplicity of changes occurring in the surroundings of libraries mean that, if they want to be seen as modern, they must adapt their products to new conditions and, especially, to the needs and expectations of users. The authors emphasize the importance of creating a culture of evaluation in the library, consisting in a readiness to conduct extensive research on the functioning of libraries, the quality of their services and the library environment. Having discussed the standards, guidelines, examples and methodology of library research on all these levels, the authors present a few selected results from user satisfaction surveys conducted at the University of Zielona Góra library, suggesting that they could serve as a starting point for building a culture of evaluation at the library.
Keywords: biblioteki; biblioteki akademickie; badania ankietowe; ewaluacja; użytkownicy bibliotek; Uniwersytet Zielonogórski; libraries; academic libraries; survey research; evaluation; library users